Cationically photopolymerizable epoxy-functionalized thermoplastic polysilsesquioxanes: synthesis and properties - Lee, A. S.; Choi, S. S.; Song, S. -J.; Baek, K. -Y.; Hwang, S. S. (ROYAL SOC CHEMISTRY, 2014)
A series of epoxy-functionalized inorganic-organic hybrid ladder-like structured polysilsesquioxanes were synthesized in one-batch via a base-catalyzed co-solvent system. Two types of epoxy functionalities were examined: aliphatic and cycloaliphatic. Obtained polymeric epoxy-functionalized ladder-like polysilsesquioxanes were cationically photopolymerized under UV irradiation over glass and plastic substrates. Obtained cross-linked films were examined as hardcoating materials as their thermal, optical, mechanical, and barrier properties were studied. These materials showed superior thermal properties (T-d > 400 degrees C), high optical transparency (>95%), high pencil hardness (4H-9H), low dielectric constant (3.0-3.6), and good barrier properties (WVTR < 10(1) g m(-2) day(-1), OTR < 10(2) g m(-2) day(-1)).
Keywords: HYBRID; SILSESQUIOXANES